Stop Insecure! Mulailah dengan Bersyukur - Muhammad Ilham Nurhakim; Saufitri Komalasari (Yayasan Aya Sophia Indonesia, 2023)
The purpose of this study is to present a review of the book Regardless of the Shadows of Insufficiency by Christine Anggaraini. This research uses a descriptive qualitative method through content analysis. This book explains how to understand insecurities and escape from them. God created humans with various advantages and disadvantages. God created it to form a balance in life. Feelings of insecurity grow under the influence of distorted mindsets and environmental influences that make you focus more on weaknesses and forget about strengths. Get to know your thoughts and fears, so you can escape the shadow of inadequacy.